Kepuasan Kerja Karyawan Pada PT Cilegon Fabricators (Divisi Engeneering) - Suhartini Suhartini (Komunitas Dosen Indonesia, 2021)
This study aims to determine employee job satisfaction at the company PT. Colegon Fabricator (Engineering Division) is located in Bojonagara, Cilegon, Banten. A company engaged in steel starting from steel structures, boilers, pressure parts, container cranes, vessels and developing its business in power plan maintenance throughout Indonesia. The main highlight in this study lies in employee job satisfaction which is influenced byvariables emotional exhaustion and work motivation. The method used in this study is a quantitative descriptive method with the number of samples used as many as 60 people are saturated samples. The types of data are primary and secondary with the collection techniques carried out through observation, questionnaires and literature studies, while for data analysis using IBM SPSS Statistics V.25 windows which includes instrument testing, classical assumption test, multiple linear regression analysis, t test and also test F. The results obtained from this study are From df1 = 2 and df2 = 58 then Ftable is 3.16. Obtained Fcount > Ftable (62,947 > 3,16) and sig F < (0.000 < 0.05). From these results, it can be concluded that Emotional Exhaustion (X1) and Work Motivation (X2) have a significant effect on Employee Job Satisfaction (Y) at PT Cilegon Fabricators